STRENGTHENING EMPLOYEE PERFORMANCE THROUGH REWARDS AND PUNISHMENT - Markus Londong; Frans Gana; Ricky Ekaputra Foeh (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the influence of reward and punishment on employee performance at CV Auto Nusa Abadi Kupang. A quantitative approach was applied using a survey method. The research population consisted of 68 employees, all of whom were included as respondents through a saturated sampling technique. Data were collected using structured questionnaires and analyzed through multiple linear regression with the assistance of SPSS software. The results reveal that rewards have a positive and statistically significant effect on employee performance. Punishment also shows a positive and significant impact on performance. Simultaneously, reward and punishment jointly influence employee performance. These findings indicate that the fair and consistent application of reward and punishment systems can effectively enhance employee performance. Therefore, organizations are encouraged to develop and strengthen reward and punishment policies to achieve better work outcomes.